2021
DOI: 10.1200/jco.2021.39.6_suppl.93
|View full text |Cite
|
Sign up to set email alerts
|

TALAPRO-1: Phase II study of talazoparib (TALA) in patients (pts) with DNA damage repair alterations (DDRm) and metastatic castration-resistant prostate cancer (mCRPC).

Abstract: 93 Background: Poly(ADP-ribose) polymerase (PARP) inhibitors (PARPi) show antitumor activity in mCRPC/DDRm pts treated with novel hormonal therapy (NHT). TALAPRO-1 is an open-label study evaluating TALA (a potent PARP inhibitor/trapper) in men with mCRPC/DDRm. We report a planned interim analysis (IA; Dec 2019). Updated results at a Sep 4 2020 cut-off, available in November 2020, will be presented at the meeting. Methods: TALAPRO-1 (NCT03148795) is enrolling pts (N ≈ 100) with measurable soft tissue disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Thus, our general approach entails consideration of the epidemiology of the disease and design of studies that reflect the age distribution, beginning with no age exclusion. For example, in some of our recent trials recruiting heavily pretreated men with metastatic castration-resistant prostate cancer, which naturally implies an advanced age group, removal of upper age cutoffs from eligibly criteria and reliance on functional measures that have a scientific rationale allowed recruitment of a trial sample with a median age of 69 years and up to 84 years (TALAPRO-1, NCT03148795) ( 26 ). Beyond data from clinical trials, we also rely on real-world evidence studies to further our understanding of treatment patterns and functional and quality-of-life outcomes in older patients; for instance, the PalomAGE study (EUPAS23012) is a prospective observational study that we recently initiated specifically to understand experience of women aged 70 years and older with locally advanced or metastatic breast cancer ( 27 ).…”
Section: Trial Eligibility and Designmentioning
confidence: 99%
“…Thus, our general approach entails consideration of the epidemiology of the disease and design of studies that reflect the age distribution, beginning with no age exclusion. For example, in some of our recent trials recruiting heavily pretreated men with metastatic castration-resistant prostate cancer, which naturally implies an advanced age group, removal of upper age cutoffs from eligibly criteria and reliance on functional measures that have a scientific rationale allowed recruitment of a trial sample with a median age of 69 years and up to 84 years (TALAPRO-1, NCT03148795) ( 26 ). Beyond data from clinical trials, we also rely on real-world evidence studies to further our understanding of treatment patterns and functional and quality-of-life outcomes in older patients; for instance, the PalomAGE study (EUPAS23012) is a prospective observational study that we recently initiated specifically to understand experience of women aged 70 years and older with locally advanced or metastatic breast cancer ( 27 ).…”
Section: Trial Eligibility and Designmentioning
confidence: 99%
“…Taza and colleagues found that PARP inhibitor activity was diminished in BRCA1 - versus BRCA2 -altered mCRPC in a cohort of 123 BRCA1/2 -altered mCRPC patients receiving the PARP inhibitor, and this differential activity was not explained by mutation origin (germline vs. somatic) or allelic status (mono- vs. biallelic) [ 120 ]. The phase II TALAPRO-1 trial reported results from the treatment with talazoparib in patients with mCRPC and associated DDR defects who had progressed after ARSi and taxane [ 99 ]. The overall response rates were 44% in patients harboring BRCA1/2 alterations, 33% in PALB2 and 12% in ATM, whereas the complete response rates were 76% in BRCA1/2 , 50% in PALB2 , and 28% in ATM.…”
Section: Predictive Biomarkers and Potential Impact On Treatment Sequencementioning
confidence: 99%
“…No response was observed in the other HRR groups. Most common adverse events were slightly more frequent than other PARPi, namely anemia (42.5%, all grades) and nausea (32.7%, all grades) [53].…”
Section: Talazoparibmentioning
confidence: 86%
“…They have received at least one taxane-based chemotherapy regimen and one or more NHT. Interim results were recently reported with 113 patients having received talazoparib and 75 patients evaluable for the primary endpoint of ORR (41 BRCA1/2, 3 PALB2, 17 ATM and 14 patients with other HRR gene alterations) [52,53]. In the BRCA, PALB2 and the ATM groups, ORR was 43.9%, 33.3% and 11.8%, respectively.…”
Section: Talazoparibmentioning
confidence: 98%